2015
DOI: 10.3109/07435800.2015.1038353
|View full text |Cite
|
Sign up to set email alerts
|

Does GLP-1 suppress its own basal secretion?

Abstract: Purpose/Aim Negative feedback controls in endocrine regulatory systems are well recognized. The incretins and their role in glucose regulation have been of major interest recently. Whether the same negative control system applies to the regulation of incretin secretion is not clear. We sought to examine the hypothesis that exogenous administration of glucagon like peptide-1, GLP-1 (7-36) amide or its metabolite GLP-1 (9-36)amide, reduces the endogenous basal release of this incretin. Materials and Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…86 Such an elevation in humans would be in line with the 2.2-fold rise in plasma GIP levels evident in our rat mTBI study and could be further augmented by continuous subcutaneous administration of exogenous GIP, as has been achieved in human studies with GLP-1 over an extended period. 87 Notably, administration of exogenous incretins does not appear to suppress their endogenous release, 88 thereby providing our studies translational potential.…”
Section: Discussionmentioning
confidence: 95%
“…86 Such an elevation in humans would be in line with the 2.2-fold rise in plasma GIP levels evident in our rat mTBI study and could be further augmented by continuous subcutaneous administration of exogenous GIP, as has been achieved in human studies with GLP-1 over an extended period. 87 Notably, administration of exogenous incretins does not appear to suppress their endogenous release, 88 thereby providing our studies translational potential.…”
Section: Discussionmentioning
confidence: 95%
“…The GLP-1 dosage selected for this study was chosen based on the preassumption that basal GLP-1 secretion would not be affected in a negative feedback loop, as previously reported. 32 Chronic GLP-1 intraperitoneal administration did not induce any significant change in body weight, body weight gain, or food intake in SHAM-GLP1 or VGX-GLP1 when compared with the respective controls. GLP-1 has a well-established role in the regulation of food intake and body weight that is partially dependent of the vagus nerve integrity, 13 although GLP-1R agonists were also reported to exert these effects through direct action on the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Such autocrine feedback may be operative also in GLP-1-secreting cells, where GLP-1R expression on L-cells and its involvement in GLP-1 secretion has previously been suggested by data from in vivo and in vitro studies [77,121]. Although a recent study indicated that GLP-1 and its degradation products do not modulate L-cell basal secretion of GLP-1(7-36) amide, any potential feedback mechanisms acting on post prandial responses were not investigated [122].…”
Section: Neuroendocrine Signalsmentioning
confidence: 92%